O uso de razões e proporções enquanto ferramenta de defesa do consumidor - SILVA, Daniel Conceição Mendonça da (2023)
The theme of this work is how to make use of Ratios and Proportions as a consumer protection tool. It is considered that this subject is of extreme relevance since it is capable of demonstrating that Mathematics is a prosperous field, contextualized and applicable to the life and day-to-day of all people. To produce the work, bibliographical research is used regarding what the Common National Curricular Base and the National Curricular Parameters recommend, as well as what is contained in the textbooks of the 7th year of Elementary School chosen by the Guide of the National Book Program and the Didactic Material (PNLD) of 2020, in addition to other authors who debate the issue. Law No. 8,078, of September 11, 1990 – on consumer rights – is also used as a tool to show where consumers are supported and how, through mathematical knowledge, they can be able to supervise and understand whether they are being respected at all times. make purchases. It is concluded that knowledge about Ratios and Proportion matters proved to be useful in the inspection process and conscious purchases.